A Educação do Campo na perspectiva do desenvolvimento rural: um estudo de caso de duas escolas rurais da região noroeste do estado do Rio Grande do Sul - Guedes, Ana Cecilia (2015)
This dissertation develpos a case study of two rural schools of the state school system, that use in their dynamic teaching and learning the methodological framework of Rural Education, aiming the training of citizens aware of their roles in society. In recent decades through the struggle of social movements to Rural Education has been inserted in public policies, seeking to re-create the relationship between field and the city. This study was developed at the State Elementary School Holy Spirit, located in Alegria - RS and at the State Elementary School Duque de Caxias, located in Independence - RS and had as the general objective to understand how the process of institutionalization of public policy Rural Education can contribute to the change in the formation of the subjects of the field. In this sense, we conducted a survey in which the qualitative methodology was used to understand the results of this research. We made use of the monitoring techniques, informal interviews, questionnaires and document analysis. Students were interviewed, educators, employees and the community (parents), thus seeking to achieve the objective of this research. We got as results, educators committed to a differentiated training aimed at the enhancement of local knowledge, intent on the part of students to remain in rural areas, and the development of environmental awareness, and by parents, the value of this educational process. Some difficulties were noted as adapting laws and bureaucratic rules which ends up making the work impossible sometimes by hiring "temporary teachers" not committed to this educational process.